Metals-triggered compound CDPDP exhibits anti-arthritic behavior by downregulating the inflammatory cytokines, and modulating the oxidative storm in mice models with extensive ADMET, docking and simulation studies - Hassan, Syed Shams ul; Abbas, Syed Qamar; Muhammad, Ishaq; Wu, Jia-Jia; Yan, Shi-Kai; Ali, Fawad; Majid, Muhammad; Jin, Hui-Zi; Bungau, Simona (Frontiers in Pharmacology, 2022)
Triggering through abiotic stress, including chemical triggers like heavy metals, is a new technique for drug discovery. In this research, the effect of heavy metal Nickel on actinobacteria Streptomyces sp. SH-1327 to obtain a stress-derived compound was firstly investigated. A new compound cyclo-(D)-Pro-(D)-Phe (CDPDP) was triggered from the actinobacteria strain SH-1327 with the addition of nickel ions 1mM. The stress compound was further evaluated for its anti-oxidant, analgesic, and anti-inflammatory activity against rheumatoid arthritis through in-vitro and in-vivo assays in albino mice. A remarkable in-vitro anti-oxidant potential of CDPDP was recorded with the IC50 value of 30.06±5.11 µg/mL in DPPH, IC50 of 18.98±2.91 against NO free radicals, the IC50 value of 27.15±3.12 against scavenging ability and IC50 value of 28.40±3.14µg/mL for iron chelation capacity. Downregulation of pro-inflammatory mediators (NO and MDA), suppressed levels of pro-inflammatory cytokines (TNF-α, IL-6, IL-Iβ) and upregulation of expressions of anti-oxidant enzymes (GSH, catalase, and GST) unveiled its anti-inflammatory potential. CDPDP was analyzed in human chondrocyte cell line CHON-001 and the results demonstrated that CDPDP significantly increased cell survival, and inhibited apoptosis of IL-1β treated chondrocytes and IL-1β induced matrix degrading markers. In addition, to evaluate the mitochondrial fitness of CHON-001 cells, CDPDP significantly upregulated pgc1-α, the master regulator of mitochondrial biogenesis, indicating that CDPDP provides protective effects in CHON-001 cells. The absorption, distribution, metabolism, excretion, and toxicity (ADMET) profile of the CDPDP showed that CDPDP is safe in cases of hepatotoxicity, cardiotoxicity, and cytochrome inhibition. Furthermore, docking results showed good binding of CDPDP with IL-6 -17.4kcal/mol, and the simulation studies proved the stability between ligand and protein. Therefore, the findings of the current study prospect CDPDP as a potent anti-oxidant and a plausible anti-arthritic agent with a strong pharmacokinetic and pharmacological profile.